Case managers’ reflections of a brief case management intervention in Canada - Duncan, Andrea; Kirst, Maritt; Dainty, Katie N.; Wodchis, Walter P.; Stergiopoulos, Vicky (Frontiers in Psychiatry, 2023)
Introduction: As demand for intensive case management services continues to outpace supply, community mental health agencies in Toronto, Ontario, introduced Short-Term Case Management (STCM). Objective: This study sought to explore case managers’ perspectives and experiences with this new service delivery model. Methods: Focus groups were conducted, and transcripts analyzed using thematic analysis. Results: Emerging themes suggest that despite embracing a recovery approach, case managers expressed mixed views on the acceptability and appropriateness of this service delivery model as an intervention. Conclusions: The ideal population for this intervention are adults with mental health issues in need of system navigation, and those motivated to address their goals. Further research is needed to establish fidelity criteria.